An Applied Study of the Symmetric and Asymmetric Impact of Oil Prices and International Financial Markets on Economic Growth in Iraq - Khaleel, Moustfa Ismael; Jabbar, Ahmed Younis; Kalai, Maha; Aloulou, Rima; Helali, Kamel (International Journal of Energy Economics and Policy, 2024)
Iraq, one of the main oil exporting nations, is extremely susceptible to changes in the price of oil. This article attempts to investigate how the price of oil affects the way the Iraqi economy performs, as indicated by a number of factors (economic growth and international financial markets). We will apply econometric techniques in both linear and non-linear frameworks to accomplish this goal. To represent NARDL non-linearities in the relationship between the aforementioned economic variables, we will first look for linear cointegrating correlations and/or estimate ARDL models. If necessary, we will next use threshold cointegration. Thus, we demonstrate that, independent of the regime we are in, the asymmetry associated with the shock's sign is confirmed over the span January 2006–December 2020. Regarding the asymmetry associated with the shock's magnitude, it is only confirmed under the "below oil price threshold regime." In the "above oil price threshold regime," yields respond in a way that is proportionate to the shock's magnitude. Additionally, we demonstrate that the asymmetry associated with the shock's sign is confirmed during times of negative industrial output growth, while the influence of shocks looks symmetrical during times of positive industrial production variation.